Industrial upgrade and economic governance in the Pearl River Delta: A case study of Dongguan city - Zhifeng Wang; Xiaoming Xu; Zhiqing Liang (China Finance and Economic Review, 2016)
The Pearl River Delta, one of the main regions of China's export-oriented economy, has benefited from its traditional economic structure for three decades which in turn appeared to hinder further economic development recently. To advance industrial restructuring and upgrading, the governments have promulgated policies and appropriated special funds to optimize the industrial structure of the Pearl River Delta. Dongguan is a famous export-oriented and manufacturing city in China. Taking Dongguan city as a case, and applying the method of Difference-in-Difference (DID), using time-series data from 1997 to 2014, this article analyzes the policy benefits of Dongguan's industrial transformation and upgrading, aiming to not only examine the effectiveness of industrial upgrades and the effects of economic governance in the Pearl River Delta but provide some reference to other export-oriented regions of China.
Keywords: 330; Industrial upgrade; Economic governance; Industrial policy valuation